The quadruple innovation helix nexus : a smart growth model, quantitative empirical validation and operationalization for OECD countries - Monteiro, Sara Paulina de Oliveira; Carayannis, Elias G. (Palgrave studies in democracy, innovation, and entrepreneurship for growth., 2017)
The Quadruple Innovation Helix concept is the synthesis of top-down policies and practices from Government, University and Industry balanced and shaped by bottom-up initiatives and actions by Civil Society. In addition, of significance is the complementary expansion and completion of the Quadruple Innovation Helix by the concept of the Quintuple Innovation Helix, to which an all-encompassing fifth dimension was added, namely, the Environment. This book expertly defines the impact of public policies and productive public expenditures on innovation and economic growth in the Organization for Economic Cooperation and Development (OECD) countries. Economic growth is managed by the creation of differentiated productive units that interact with each other and complement each other in the production of continuous innovation. This book provides a theoretical model of economic growth to demonstrate the importance of governments in promoting innovation. It is a seminal read which scholars, governments, and NGOs will find greatly beneficial.- Resumé vydavatel